Understanding of Disaster Fiqh in the Matter of Worship in Times of Natural Disasters (Study in Tanjung Raya District, Religious Regency, West Sumatra) - Halim, Syaflin; Desminar, Desminar; Syamsurizal, Syamsurizal; Yanti, Elma Rida; Habibullah, Habibullah (Jurnal Kajian dan Pengembangan Umat, 2025)
Abstract Natural disasters such as floods and earthquakes often hinder the normal implementation of worship, especially in terms of purification and prayer. However, the public's understanding of the leniency (rukhsah) of worship regulated in Islamic jurisprudence is still limited, including in the Tanjung Raya area, West Sumatra. This research aims to reveal the extent of public understanding of the implementation of worship in emergency conditions and how fatwas and fiqh principles can be implemented in the context of disasters. This study uses a qualitative-descriptive method with in-depth interview techniques with community leaders, as well as document analysis of fatwas of the Indonesian Ulema Council (MUI) and disaster fiqh literature. The results of the study show that the majority of people have the spirit of carrying out worship but have not fully understood the leniency such as tayammum, praying in unclean clothes, praying plural, or performing prayers in a state of awrah that is not completely covered. The lack of counseling and socialization is the main factor in this low understanding. Therefore, systematic disaster fiqh education is needed by religious authorities and related institutions so that people can continue to worship legally and in accordance with sharia in emergency situations. Keywords: Disaster Fiqh, Worship in Emergencies, Islamic Jurisprudence